Intelligent bolt with stress sensor

By using Ni-Co-Fe-Mo-Al high-entropy alloy material and multi-layer structural stress sensor in intelligent bolts, the problem of insufficient fatigue and fracture resistance in high-strength fasteners is solved, and the stress state is achieved Inspection and monitoring improve the performance of the bolt and are suitable for high-strength connections in complex environments.

CN222185375UActive Publication Date: 2024-12-17WUHAN JIALIAN SENSING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420409588.5
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2024-12-17
Estimated Expiration
2034-03-04

AI Technical Summary

Technical Problem

The prior art lacks effective fatigue and fracture resistance research in high-strength fasteners, especially in complex environments, and high-entropy alloys have not yet entered the practical application stage in fastener applications.

Method used

A smart bolt with stress sensor was designed, using Ni-Co-Fe-Mo-Al high-entropy alloy material, combining layer structures of layer, support layer, piezoelectric functional layer and wear-resistant electrode layer, through ZnO coating and The nano-multi-layer ceramic layer improves the bonding performance of the stress sensor and the bolt body, realizing the detection and monitoring of stress states.

Benefits of technology

It realizes stress state detection and monitoring of the application process, improves the fatigue resistance and wear resistance of the bolts, has ultra-high strength, and is suitable for high-strength connection requirements in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222185375U_ABST
    Figure CN222185375U_ABST
Patent Text Reader

Abstract

The utility model discloses an intelligent bolt with a stress sensor, which belongs to the technical field of intelligent bolts and comprises a bolt body, the stress sensor is arranged at the head of the bolt body, and the stress sensor comprises a bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer which are sequentially stacked from inside to outside. The bonding layer is a coating made of the same material as the bolt body; the piezoelectric functional layer is a ZnO coating; the supporting layer is a nano multilayer ceramic layer formed by alternately laminating a first nano ceramic layer and a second nano ceramic layer. The beneficial effects of the utility model are that the bolt body is sequentially provided with the bonding layer, the supporting layer, the piezoelectric function layer and the wear-resistant electrode layer to form a layer structure of a stress sensor, and the supporting layer is a nanometer multilayer ceramic layer formed by alternately laminating the first nanometer ceramic layer and the second nanometer ceramic layer. The combination performance of the stress sensor and the bolt body is effectively improved, and the stress state in the application process is detected and monitored.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of intelligent bolts, and in particular to an intelligent bolt with a stress sensor. Background Art

[0002] In fastener manufacturing, the correct selection of fastener materials is a very important link, because the performance of fasteners is closely related to their materials; if the material is selected improperly or incorrectly, it may cause the performance to fail to meet the requirements, shorten the service life, and even cause accidents or processing difficulties, high manufacturing costs, etc. Therefore, the selection of fastener materials is a very important link.

[0003] Today, advanced manufacturing represented by large aircraft, large power generation equipment, automobiles, high-speed trains, large ships, and large complete sets of equipment has become an important development direction, and fasteners have also entered an important development stage. Bolts with a performance grade of 8.8 or above are called high-strength bolts. High-strength bolts can withstand greater loads than ordinary bolts of the same specification. They are mostly used for the connection of bridges, rails, high-voltage and ultra-high-voltage equipment. The fracture of this type of bolt is mostly brittle fracture. In order to ensure the sealing of the container, high-strength bolts used in ultra-high-voltage equipment need to be subjected to a large prestress.

[0004] The current national standard only lists M39. For large-size specifications, especially high-strength bolts with a length greater than 10 to 15 times, there are no related products in China. High-strength bolts are often used in the connection of bridges, rails, high-pressure and ultra-high-pressure equipment. The materials include alloy steels such as 40Cr, 42CrMo, and carbon steels such as 8.8, 10.9, and 12.9. 0Cr has a certain toughness and hardness, and the price is relatively low. It is suitable for general high-strength applications; 42CrMo has high strength and toughness, and is suitable for occasions with large loads and impacts; 45# steel has good hardness and wear resistance, but is relatively brittle, and is mostly used to manufacture nuts and stud rods; 35CrMo has good strength and toughness, and is suitable for manufacturing high-strength bolts with high requirements and greater pressure; 20CrMoTi titanium alloy reinforced material, light material, corrosion and wear resistance, excellent strength and toughness. If it is divided by strength grade, 8.8 grade carbon steel is suitable for general structural connections; 10.9 grade carbon steel has higher strength and is suitable for higher strength structural connections; 12.9 grade carbon steel has very high strength and is suitable for applications with very strict strength requirements. In general, if the application environment is complex, you should choose corrosion-resistant and wear-resistant materials; if you need to withstand greater pressure, you should choose high-strength materials; if you need to withstand tensile conditions, you need to choose high-strength and tough materials. However, there are few studies on fasteners with a tensile strength of more than 1500MPa, and no relevant research reports have been seen. In particular, there are fewer studies on high-strength fasteners that are resistant to fatigue fracture in fields such as wind power generation.

[0005] High-entropy alloys (HEAs) are a new type of material with excellent performance. They have attracted widespread attention from the scientific community for their excellent mechanical properties, corrosion resistance, and excellent thermal stability. High-entropy alloys are crystals composed of more than five elements, with atoms of each element randomly occupying a lattice site. Ye Junwei et al. discovered alloys with a face-centered cubic solid solution structure represented by CoCrCuFeNi; Zhang Yong et al. discovered alloys with a body-centered cubic solid solution structure represented by A1CoCrFeNi. Today, the concept of high entropy is widely used in various materials such as oxides, chalcogenides, and halides. The fracture of materials is often related to safety issues. Generally speaking, it can be divided into brittle and ductile fractures according to the failure strain. Brittle fracture has no signs of plastic deformation and usually occurs in a catastrophic manner. It is of great significance to develop new metal materials with excellent tensile and fatigue properties. It is reported that when the temperature drops from 298K to 77K, the fracture toughness of CrMnFeCoNi high-entropy alloy remains almost constant, while the fracture toughness of CrCoNi high-entropy alloy increases slightly. In these HEAs, there is no sharp ductile-brittle transition as seen in many conventional alloys such as steel, amorphous alloys, magnesium alloys, porous metals, and nanometals, suggesting that these alloys may be excellent candidates for applications in extreme cold conditions, such as materials for ship hulls, aircraft, and cryogenic storage tanks.

[0006] High entropy alloys have the characteristics of high hardness and high strength, and can be widely used in many fields such as motors, transformers, machine tools, consumer electronics, engine blades, jet engines, etc. High entropy alloys are a brand-new alloy field. They jump out of the design framework of traditional alloys and are special alloy systems with many excellent properties. Adjusting its composition can further optimize the performance, so it has extremely broad application prospects. Domestic research on high entropy alloy fasteners has just started. Although many researchers have begun to pay attention to the research of such alloys, the relevant data is still in the laboratory stage and has not really entered the practical application stage.

[0007] In view of this, the inventor conducted in-depth research on this demand, and thus the present case was produced. Utility Model Content

[0008] The utility model designs an intelligent bolt structure with a stress sensor, which can detect and monitor the stress state of the application process, and has important value for the anti-fatigue and anti-fracture fastening connection requirements in complex environments. The specific technical solution is as follows:

[0009] A smart bolt with a stress sensor comprises a bolt body, a head of the bolt body is provided with a stress sensor, and the stress sensor comprises a bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer which are sequentially stacked from inside to outside;

[0010] The bonding layer is a coating made of the same material as the bolt body; the piezoelectric functional layer is a ZnO coating; and the supporting layer is a nano-multilayer ceramic layer formed by alternately stacking a first nano-ceramic layer and a second nano-ceramic layer.

[0011] A bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer are sequentially arranged on the bolt body to form a layer structure of a stress sensor, and the material of the bonding layer is set to a coating of the same material as the bolt body, the supporting layer is set to a nano multilayer ceramic layer formed by alternating stacking of a first nano ceramic layer and a second nano ceramic layer, and the piezoelectric functional layer is set to a ZnO coating, which effectively improves the bonding performance between the stress sensor and the bolt body, realizes the detection and monitoring of the stress state in the application process, and has certain reference significance for the layer structure design of stress sensors in smart bolts of different materials.

[0012] The supporting layer adopts a nano multi-layer ceramic layer, which not only improves the hardness of the coating, but also is a metal-ceramic composite material with lower stress.

[0013] Preferably, the material of the first nano-ceramic layer is the same as that of the bolt body, and the material of the second nano-ceramic layer is the same as that of the wear-resistant electrode layer.

[0014] Preferably, the thickness of a single-layer first nano-ceramic layer on the support layer is 10-20 nanometers, and the thickness of a single-layer second nano-ceramic layer is 5-10 nanometers.

[0015] Preferably, the piezoelectric functional layer has a thickness of 7000-13000 nanometers.

[0016] Preferably, the crystal structure of the piezoelectric functional layer is columnar crystals, and the diameter of the columnar crystals is 0.5-2.0 microns.

[0017] Preferably, the wear-resistant electrode layer has a thickness of 1-20 micrometers, and the coating thickness of the bonding layer is 20-100 nanometers.

[0018] Preferably, the bolt body is made of Ni-Co-Fe-Mo-Al high entropy alloy, the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline alloy coating, and the nanocrystalline grain size is 10-20 nanometers.

[0019] Preferably, the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high entropy alloy conductive ceramic coating. The bolt body is made of Ni-Co-Fe-Mo-Al high entropy alloy, which makes the bolt have ultra-high strength and fatigue resistance. The wear-resistant electrode layer uses Ni-Co-Fe-Mo-Al-N high entropy alloy conductive ceramic coating, which not only solves the problem of low hardness and poor friction resistance of traditional materials such as Ti, Cr and silver, but also greatly improves the hardness of the electrode, thereby greatly improving its wear resistance.

[0020] Preferably, the support layer is formed by stacking a first nano-ceramic layer and a second nano-ceramic layer; the thickness of a single first nano-ceramic layer is 10 nanometers, and the thickness of a single second nano-ceramic layer is 5 nanometers.

[0021] Preferably, a groove is formed on the head of the bolt body, and the stress sensor is located in the groove, which can protect the stress sensor from being damaged.

[0022] Beneficial effects:

[0023] The technical solution of the utility model has at least the following beneficial effects:

[0024] (1) A bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer are sequentially arranged on the bolt body to form a layer structure of a stress sensor, and the material of the bonding layer is set to a coating of the same material as the bolt body, the supporting layer is set to a nano-multilayer ceramic layer formed by alternating a first nano-ceramic layer and a second nano-ceramic layer, and the piezoelectric functional layer is set to a ZnO coating, which effectively improves the bonding performance between the stress sensor and the bolt body, realizes the detection and monitoring of the stress state in the application process, and has a certain reference significance for the layer structure design of stress sensors in smart bolts of different materials.

[0025] (2) The bolt body is made of Ni-Co-Fe-Mo-Al high entropy alloy, which makes the bolt have ultra-high strength and fatigue resistance. The wear-resistant electrode layer uses Ni-Co-Fe-Mo-Al-N high entropy alloy conductive ceramic coating, which not only solves the problem of low hardness and poor friction resistance of traditional materials such as Ti, Cr and silver, but also greatly improves the hardness of the electrode, thereby greatly improving its wear resistance.

[0026] (3) The support layer adopts a nano-multilayer ceramic layer, which not only improves the hardness of the coating, but also is a metal-ceramic composite material with lower stress. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the implementation mode of the utility model, the drawings required for use in the implementation mode will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the utility model and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a schematic diagram of the structure of the fatigue-fracture-resistant high-strength high-entropy alloy fastener in the utility model;

[0029] Figure 2 It is a schematic diagram of the piezoelectric thin film coating device in the utility model;

[0030] Figure 3 It is a schematic diagram of the structure of the stress sensor layer in the utility model;

[0031] Figure 4 It is a schematic diagram of the high entropy alloy fastener in the utility model. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the utility model clearer, the technical solutions in the embodiments of the utility model will be clearly and completely described below in conjunction with the drawings in the embodiments of the utility model. Obviously, the described embodiments are part of the embodiments of the utility model, not all of the embodiments. Therefore, the following detailed description of the embodiments of the utility model provided in the drawings is not intended to limit the scope of the utility model for which protection is sought, but merely represents the selected embodiments of the utility model. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the utility model.

[0033] In this embodiment, a bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer are sequentially arranged on the bolt body to form a layer structure of a stress sensor, and the material of the bonding layer is set to a coating of the same material as the bolt body, the supporting layer is set to a nano multilayer ceramic layer formed by alternating the first nano ceramic layer and the second nano ceramic layer, and the piezoelectric functional layer is set to a ZnO coating, which effectively improves the bonding performance between the stress sensor and the bolt body, realizes the detection and monitoring of the stress state during the application process, and has a certain reference significance for the layer structure design of stress sensors in smart bolts of different materials. The specific implementation is as follows:

[0034] A smart bolt with a stress sensor comprises a bolt body, a head of the bolt body is provided with a stress sensor, and the stress sensor comprises a bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer which are sequentially stacked from inside to outside;

[0035] The bonding layer is a coating made of the same material as the bolt body; the piezoelectric functional layer is a ZnO coating; and the supporting layer is a nano-multilayer ceramic layer formed by alternately stacking a first nano-ceramic layer and a second nano-ceramic layer. The supporting layer is a nano-multilayer ceramic layer, which not only improves the hardness of the coating, but also is a metal-ceramic composite material with lower stress.

[0036] As a preferred implementation manner, the material of the first nano-ceramic layer is the same as that of the bolt body, and the material of the second nano-ceramic layer is the same as that of the wear-resistant electrode layer.

[0037] As a preferred embodiment, the modulation period of the support layer is 15-30 nanometers, the thickness of the upper single-layer first nano-ceramic layer is 10-20 nanometers, and the thickness of the upper single-layer second nano-ceramic layer is 5-10 nanometers.

[0038] As a preferred implementation, the piezoelectric functional layer is a ZnO coating co-doped with a ternary alloy of V, Fe and Cr, and the thickness of the piezoelectric functional layer is 7000-13000 nanometers.

[0039] As a preferred embodiment, the coating layer of the piezoelectric functional layer has a (002) crystal orientation, a columnar crystal structure, and a columnar crystal diameter of 0.5-2.0 microns.

[0040] As a preferred embodiment, the thickness of the wear-resistant electrode layer is 1-20 micrometers, and the coating thickness of the bonding layer is 20-100 nanometers.

[0041] As a preferred embodiment, the material of the bolt body is Ni-Co-Fe-Mo-Al high entropy alloy, and the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline alloy coating with a (110) crystal plane preferential orientation, and the nanocrystalline grain size is 10-20 nanometers.

[0042] As a preferred embodiment, the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high entropy alloy conductive ceramic coating. The bolt body is made of Ni-Co-Fe-Mo-Al high entropy alloy, which makes the bolt have ultra-high strength and fatigue resistance. The wear-resistant electrode layer uses Ni-Co-Fe-Mo-Al-N high entropy alloy conductive ceramic coating, which not only solves the problem of low hardness and poor friction resistance of traditional materials such as Ti, Cr and silver, but also greatly improves the hardness of the electrode, thereby greatly improving its wear resistance.

[0043] As a preferred embodiment, the support layer is formed by stacking a first nano-ceramic layer and a second nano-ceramic layer; the thickness of a single first nano-ceramic layer is 10 nanometers, and the thickness of a single second nano-ceramic layer is 5 nanometers.

[0044] As a preferred implementation, a groove is formed on the head of the bolt body, and the stress sensor is located in the groove, which can protect the stress sensor from being damaged.

[0045] like Figure 1 The figure shows a schematic diagram of a fatigue-fracture-resistant high-strength high-entropy alloy fastener of the present invention. The stress sensor 103 is on the head 101 of the fastener 100. The head 101 is processed with a groove 102. The stress sensor 103 is prepared in the groove. The purpose of the groove 102 is to protect the stress sensor 103 from being damaged.

[0046] Figure 2 The device used in the utility model is shown, and the vacuum chamber of the device is surrounded by the furnace wall. The vacuum chamber is provided with an exhaust port 4, and the vacuum pumping unit evacuates the vacuum chamber through the exhaust port 4. The four corners of the vacuum chamber are heaters 3, and the heating power is 30 kilowatts to improve the heating efficiency. Three targets are installed on the furnace wall in three rows, one is an etching Cr target 1, one is a Ni-Co-Fe-Mo-Al coating arc target 2 and one is a ZnVFeCrO ​​target 6, and the sample 7 is installed on the workpiece rack 5. This layout greatly increases the plasma density in the vacuum chamber, and the workpiece is completely immersed in the plasma. The deposition rate, hardness and adhesion of the coating are greatly improved. Due to the optimization of the target structure, the magnetic field distribution is more uniform, the magnetron sputtering target surface is etched evenly, and the uniformity of the coating is improved.

[0047] Figure 3 The schematic diagram of the coating structure designed for the utility model shows that there are composition and hardness gradients in the coating structure, which reduces the stress of the coating and allows the deposition of thicker piezoelectric coatings. The coating structure includes a substrate 10, and a Ni-Co-Fe-Mo-Al high entropy bonding layer 20, a Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N high entropy nano multilayer support layer 30, a ZnVFeCrO ​​piezoelectric functional layer 40, and a Ni-Co-Fe-Mo-Al-N high entropy ceramic conductive layer 50 sequentially deposited on the surface of the substrate 10;

[0048] The Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N high entropy nano multilayer support layer 30 is composed of alternately stacked Ni-Co-Fe-Mo-Al layers 31 and Ni-Co-Fe-Mo-Al-N layers 32.

[0049] Figure 4This is a microstructure diagram of the high entropy alloy material after solid solution + failure treatment in the utility model.

[0050] The beneficial effects of the fatigue fracture resistant high entropy alloy fastener and its preparation process in the present invention are further reviewed through several groups of embodiments and comparative examples.

[0051] Embodiment 1:

[0052] The preparation process of the fatigue fracture resistant high entropy alloy fastener in this embodiment includes the following steps:

[0053] Step 1: melt the Ni-Co-Fe-Mo-Al high entropy alloy material into a 8 mm rod, and perform solid solution and failure treatment. The solid solution temperature is 800°C and the holding time is 2 hours; the failure temperature is 400°C and the holding time is 4 hours;

[0054] Step 2: The rod after the solid solution failure treatment is made into a fastener matrix by high temperature forging and high temperature thread rolling, the forging temperature is 800°C, and the thread rolling temperature is 300°C; and the head of the fastener matrix is ​​polished;

[0055] Step 3: depositing a bonding layer in an argon environment by arc ion plating technology at 1 Pa and 50 V; the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline bonding layer with a preferred orientation of the (110) crystal plane, the nanocrystalline grain size is 10 nanometers, and the coating thickness is 20 nanometers;

[0056] The support layer is deposited by arc ion plating in an argon + nitrogen environment at 1Pa and 50V, and the Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N nano multilayer film is formed by intermittently introducing nitrogen; the modulation period is 15 nanometers, the thickness of a single Ni-Co-Fe-Mo-Al layer is 10 nanometers, and the thickness of a single Ni-Co-Fe-Mo-Al-N layer is 5 nanometers;

[0057] A piezoelectric functional layer is deposited under the conditions of 0.5 Pa and 10 V, which is a piezoelectric material co-doped with a ternary alloy of V, Fe, and Cr, wherein the V content is 0 at.%, the Fe content is 1 at.%, and the Cr content is 1 at.%. The coating has a (002) crystal orientation, a columnar crystal structure, and a columnar crystal diameter of 0.5 micrometers.

[0058] In a nitrogen environment, a wear-resistant electrode layer is deposited under the conditions of 1Pa and 0V. The electrode material of the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high-entropy alloy ceramic conductive coating. The contact resistance is less than 100 ohms and the coating thickness is 1 micron.

[0059] Finally, the fatigue fracture resistant high entropy alloy fastener is obtained.

[0060] Embodiment 2:

[0061] The preparation process of the fatigue fracture resistant high entropy alloy fastener in this embodiment includes the following steps:

[0062] Step 1: melt the Ni-Co-Fe-Mo-Al high entropy alloy material into a 100 mm rod, and perform solid solution and failure treatment. The solid solution temperature is 1000°C and the holding time is 10 hours; the failure temperature is 600°C and the holding time is 10 hours;

[0063] Step 2: The rod after the solid solution failure treatment is made into a fastener matrix by high temperature forging and high temperature thread rolling, the forging temperature is 900°C, and the thread rolling temperature is 500°C; and the head of the fastener matrix is ​​polished;

[0064] Step 3: depositing a bonding layer in an argon environment by arc ion plating technology at 2 Pa and 150 V; the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline bonding layer with a preferred orientation of the (110) crystal plane, the nanocrystalline grain size is 20 nanometers, and the coating thickness is 100 nanometers;

[0065] The support layer is deposited by arc ion plating in an argon + nitrogen environment at 3Pa and 150V, and the Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N nano multilayer film is formed by intermittently introducing nitrogen; the modulation period is 30 nanometers, the thickness of a single Ni-Co-Fe-Mo-Al layer is 20 nanometers, and the thickness of a single Ni-Co-Fe-Mo-Al-N layer is 10 nanometers;

[0066] A piezoelectric functional layer is deposited under the conditions of 2Pa and 100V, which is a piezoelectric material co-doped with a ternary alloy of V, Fe and Cr, with a V content of 5at.%, a Fe content of 5at.%, and a Cr content of 10at.%; the coating has a (002) crystal orientation, a columnar crystal structure, and a columnar crystal diameter of 2 microns;

[0067] In a nitrogen environment, a wear-resistant electrode layer is deposited at 3Pa and 200V. The electrode material of the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high-entropy alloy ceramic conductive coating. The contact resistance is less than 100 ohms and the coating thickness is 20 microns.

[0068] Finally, the fatigue fracture resistant high entropy alloy fastener is obtained.

[0069] Embodiment 3:

[0070] The preparation process of the fatigue fracture resistant high entropy alloy fastener in this embodiment includes the following steps:

[0071] Step 1: melt the Ni-Co-Fe-Mo-Al high entropy alloy material into a 40 mm rod, and perform solution treatment and failure treatment. The solution temperature is 850°C and the holding time is 5 hours; the failure temperature is 450°C and the holding time is 5 hours;

[0072] Step 2: The rod after the solid solution failure treatment is made into a fastener matrix by high temperature forging and high temperature thread rolling, the forging temperature is 850°C, and the thread rolling temperature is 350°C; and the head of the fastener matrix is ​​polished;

[0073] Step 3: depositing a bonding layer in an argon environment by arc ion plating technology at 1 Pa and 100 V; the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline bonding layer with a preferred orientation of the (110) crystal plane, the nanocrystalline grain size is 15 nanometers, and the coating thickness is 30 nanometers;

[0074] The support layer is deposited by arc ion plating in an argon + nitrogen environment at 2Pa ​​and 100V, and the Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N nano multilayer film is formed by intermittently introducing nitrogen; the modulation period is 20 nanometers, the thickness of a single Ni-Co-Fe-Mo-Al layer is 10 nanometers, and the thickness of a single Ni-Co-Fe-Mo-Al-N layer is 10 nanometers;

[0075] A piezoelectric functional layer is deposited under the conditions of 1 Pa and 100 V, which is a piezoelectric material co-doped with a ternary alloy of V, Fe, and Cr, wherein the V content is 1 at.%, the Fe content is 2 at.%, and the Cr content is 1 at.%. The coating has a (002) crystal orientation, a columnar crystal structure, and a columnar crystal diameter of 1.2 microns.

[0076] In a nitrogen environment, a wear-resistant electrode layer is deposited under the conditions of 2Pa and 100V. The electrode material of the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high-entropy alloy ceramic conductive coating. The contact resistance is less than 100 ohms and the coating thickness is 10 microns.

[0077] Finally, the fatigue fracture resistant high entropy alloy fastener is obtained.

[0078] Embodiment 4:

[0079] The preparation process of the fatigue fracture resistant high entropy alloy fastener in this embodiment includes the following steps:

[0080] Step 1: melt the Ni-Co-Fe-Mo-Al high entropy alloy material into a 50 mm rod, and perform solid solution and failure treatment. The solid solution temperature is 800°C and the holding time is 6 hours; the failure temperature is 500°C and the holding time is 5 hours;

[0081] Step 2: The rod after the solid solution failure treatment is made into a fastener matrix by high temperature forging and high temperature thread rolling, the forging temperature is 850°C, and the thread rolling temperature is 350°C; and the head of the fastener matrix is ​​polished;

[0082] Step 3: depositing a bonding layer in an argon environment by arc ion plating technology at 2 Pa and 150 V; the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline bonding layer with a preferred orientation of the (110) crystal plane, the nanocrystalline grain size is 20 nanometers, and the coating thickness is 80 nanometers;

[0083] The support layer is deposited by arc ion plating in an argon + nitrogen environment at 3Pa and 150V, and the Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N nano multilayer film is formed by intermittently introducing nitrogen; the modulation period is 20 nanometers, the thickness of a single Ni-Co-Fe-Mo-Al layer is 10 nanometers, and the thickness of a single Ni-Co-Fe-Mo-Al-N layer is 10 nanometers;

[0084] A piezoelectric functional layer is deposited under the conditions of 2Pa and 10V, which is a piezoelectric material co-doped with a ternary alloy of V, Fe and Cr, with a V content of 4at.%, a Fe content of 3at.%, and a Cr content of 3at.%; the coating has a (002) crystal orientation, a columnar crystal structure, and a columnar crystal diameter of 1 micron;

[0085] In a nitrogen environment, a wear-resistant electrode layer is deposited under 3Pa and 0V conditions. The electrode material of the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high-entropy alloy ceramic conductive coating. The contact resistance is less than 100 ohms and the coating thickness is 10 microns.

[0086] Finally, the fatigue fracture resistant high entropy alloy fastener is obtained.

[0087] Embodiment 5:

[0088] The preparation process of the fatigue fracture resistant high entropy alloy fastener in this embodiment includes the following steps:

[0089] Step 1: melt the Ni-Co-Fe-Mo-Al high entropy alloy material into a 80 mm rod, and perform solid solution and failure treatment. The solid solution temperature is 1000°C and the holding time is 10 hours; the failure temperature is 600°C and the holding time is 9 hours;

[0090] Step 2: The rod after the solid solution failure treatment is made into a fastener matrix by high temperature forging and high temperature thread rolling, the forging temperature is 900°C, and the thread rolling temperature is 500°C; and the head of the fastener matrix is ​​polished;

[0091] Step 3: depositing a bonding layer in an argon environment by arc ion plating technology at 2 Pa and 50 V; the bonding layer is a Ni-Co-Fe-Mo-Al high entropy nanocrystalline bonding layer with a preferred orientation of the (110) crystal plane, the nanocrystalline grain size is 10 nanometers, and the coating thickness is 50 nanometers;

[0092] The support layer is deposited by arc ion plating in an argon + nitrogen environment at 3Pa and 150V, and the Ni-Co-Fe-Mo-Al / Ni-Co-Fe-Mo-Al-N nano multilayer film is formed by intermittently introducing nitrogen; the modulation period is 30 nanometers, the thickness of a single Ni-Co-Fe-Mo-Al layer is 20 nanometers, and the thickness of a single Ni-Co-Fe-Mo-Al-N layer is 10 nanometers;

[0093] A piezoelectric functional layer is deposited under the conditions of 0.5 Pa and 10 V, which is a piezoelectric material co-doped with a ternary alloy of V, Fe, and Cr, with a V content of 5 at.%, a Fe content of 1 at.%, and a Cr content of 1 at.%. The coating has a (002) crystal orientation, a columnar crystal structure, and a columnar crystal diameter of 1.5 microns.

[0094] In a nitrogen environment, a wear-resistant electrode layer is deposited under 3Pa and 0V conditions. The electrode material of the wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high-entropy alloy ceramic conductive coating. The contact resistance is less than 100 ohms and the coating thickness is 20 microns.

[0095] Finally, the fatigue fracture resistant high entropy alloy fastener is obtained.

[0096] The above description is only the preferred implementation of the utility model, and is not intended to limit the utility model. For those skilled in the art, the utility model can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the utility model shall be included in the protection scope of the utility model.

Claims

1. A smart bolt with a stress sensor, It is characterized in that It comprises a bolt body, the head of the bolt body is provided with a stress sensor, and the stress sensor comprises a bonding layer, a supporting layer, a piezoelectric functional layer and a wear-resistant electrode layer which are sequentially stacked from the inside to the outside; The bonding layer is a coating made of the same material as the bolt body; the piezoelectric functional layer is a ZnO coating; and the supporting layer is a nano-multilayer ceramic layer formed by alternately stacking a first nano-ceramic layer and a second nano-ceramic layer.

2. The smart bolt with stress sensor according to claim 1, It is characterized in that The material of the first nano-ceramic layer is the same as that of the bolt body, and the material of the second nano-ceramic layer is the same as that of the wear-resistant electrode layer.

3. The smart bolt with stress sensor according to claim 2, It is characterized in that The thickness of the single-layer first nano-ceramic layer of the support layer is 10-20 nanometers, and the thickness of the single-layer second nano-ceramic layer is 5-10 nanometers.

4. The smart bolt with a stress sensor according to claim 1, It is characterized in that The thickness of the piezoelectric functional layer is 7000-13000 nanometers.

5. The smart bolt with stress sensor according to claim 4, It is characterized in that The crystal structure of the coating layer of the piezoelectric functional layer is columnar crystals, and the diameter of the columnar crystals is 0.5-2.0 microns.

6. The smart bolt with a stress sensor according to claim 1, It is characterized in that The wear-resistant electrode layer has a thickness of 1-20 micrometers, and the coating thickness of the bonding layer is 20-100 nanometers.

7. The smart bolt with a stress sensor according to claim 2, It is characterized in that The material of the bolt body is Ni-Co-Fe-Mo-Al high entropy alloy, and the bonding layer is Ni-Co-Fe-Mo-Al high entropy nanocrystalline alloy coating, and the nanocrystalline grain size is 10-20 nanometers.

8. The smart bolt with stress sensor according to claim 7, It is characterized in that The wear-resistant electrode layer is a Ni-Co-Fe-Mo-Al-N high entropy alloy conductive ceramic coating.

9. The smart bolt with stress sensor according to claim 8, It is characterized in that The support layer is formed by stacking a first nano-ceramic layer and a second nano-ceramic layer; the thickness of a single first nano-ceramic layer is 10 nanometers, and the thickness of a single second nano-ceramic layer is 5 nanometers.

10. The smart bolt with a stress sensor according to claim 1, It is characterized in that A groove is formed on the head of the bolt body, and the stress sensor is located in the groove.